Desenvolvimento territorial e combate à pobreza rural: um estudo sobre a execução do Programa Agroamigo no município de Anajatuba – MA no período de 2013 a 2018. - ERICEIRA, Marcelo do Carmo Carvalho (2020)
This study aimed to understand the performance of rural credit for the municipality of Anajatuba-MA, from resources of the National Program for Strengthening Family Farming-PRONAF, operated by the BNB Agroamigo Microcredit Program, as well as its contribution to the socioeconomic development of the municipality. They were unveiled as innovations of rural microcredit from concepts based on considerable bibliographic sources. It was discussed about a configuration of this tool in the highlighted municipality, validation of indicators of measurement and inequality of credit destination, from the use of secondary data retrieved at the Central Bank of Brazil-BACEN and Brazilian Institute of Geography and Statistics-IBGE. In principle, it raises the theme of microcredit, punctuating important moments, since its economy in the world until its adoption in the Brazilian particularity, since it has become an important strategy in the context of public policies to confront rural poverty in Brazil. The Agroamigo Microcredit Program is far beyond a financial service as it has a major social impact, with a proposal to tackle rural poverty and reduce social inequalities that affect income generation and agricultural incomes. From the data analyzed, it can be seen if the municipality of Anajatuba has access to rural credit resources in its predominance through Agroamigo Program operations, therefore, rural microcredit. Regarding credit inequality, a survey pointed to the municipality that received this type of resource in greater proportion than its share in the Gross Domestic Product-GDP of Baixada Maranhense and Maranhão. Another important finding is that, although the municipality has increased its share of credit distribution in the context of the Baixada Maranhense, the downward trend in the share of GDP in this micro region.